Kontradiksi Pelaporan Keuangan Zakat PSAK No.109 Tentang Akuntansi Zakat, Infaq, dan Sedekah dengan Aplikasi SIMBA pada BAZNAS Kabupaten Jember - Nia Damayanti Putri Pratama; Muhammad Syarofi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine discrepancies in financial reporting of zakat under PSAK No. 109 compared to the SIMBA application and the implementation of zakat accounting at BAZNAS Kabupaten Jember. The research method used is qualitative, specifically a case study approach. Data were obtained from relevant institutional documents related to the research issue and through interviews with treasurers and amils responsible for BAZNAS fund distribution in Kabupaten Jember. The findings reveal that discrepancies exist in financial information at BAZNAS between the physical financial report recordings and the financial reports in the SIMBA application. These discrepancies are attributed to negligence on the part of BAZNAS staff in accurately inputting data into the SIMBA application and the loss of zakat distribution reports. Consequently, there are inconsistencies between the financial information recorded in the zakat distribution financial statements and the information in the SIMBA application. To address these discrepancies, BAZNAS managers or amils adjust the financial reports of zakat fund distributions in the SIMBA application. However, as of May 2023, the financial reports of zakat distribution in SIMBA and the physical record keeping still do not match. This is due to the lack of re-recording or adjustment journal entries, exacerbated by a reshuffle in the BAZNAS Jember management.